2012
DOI: 10.3233/nre-2012-00807
|View full text |Cite
|
Sign up to set email alerts
|

Effects of virtual reality on upper extremity function and activities of daily living performance in acute stroke: A double-blind randomized clinical trial

Abstract: Aim: To examine the effects of conventional therapy (CT) combined with intensive virtual reality (VR) program on upper extremity function and activities of daily living (ADL) in individuals in the acute stage of stroke. Method: Twenty-six individuals were randomly assigned to the control or experimental group. The control group received CT, while the experimental group received VR training in addition to CT on same day. The Fugl-Meyer Assessment (FMA) and the Manual Function Test (MFT) were used to measure imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
62
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(69 citation statements)
references
References 8 publications
4
62
1
2
Order By: Relevance
“…When combined, the TR and the RFVE treatments seem to regain a better motor function compared to the recovery induced by the simple augmenting of the conventional rehabilitation program intensity. The RFVE showed significant better effects than conventional treatment, confirming the evidence coming from previous studies [27, 29, 32, 35]. Indeed, also kinematic outcomes showed a significant improvement, after the RFVE than the TR treatment.…”
Section: Discussionsupporting
confidence: 88%
“…When combined, the TR and the RFVE treatments seem to regain a better motor function compared to the recovery induced by the simple augmenting of the conventional rehabilitation program intensity. The RFVE showed significant better effects than conventional treatment, confirming the evidence coming from previous studies [27, 29, 32, 35]. Indeed, also kinematic outcomes showed a significant improvement, after the RFVE than the TR treatment.…”
Section: Discussionsupporting
confidence: 88%
“…Kwon et al the indicated no benefit for intensive VR programs combined with conventional techniques in the acute phase of stroke, compared to conventional techniques alone. No significant difference was observed in ADL performance and upper extremity function [16]. In our study, the comparison of pre-treatment and posttreatment values for both groups were significant, except for SIS.…”
Section: Discussioncontrasting
confidence: 52%
“…Nintendo Wii has been suggested as an easily accessible complementary device for improving conventional therapy specially in the subacute stage of stroke rehabili-S tation in subjects with moderate strength and upper limb functional limitations [15][16][17]. In addition, VR training could be advantageous in improving the voluntary function of the arm during the acute stage of stroke in subjects participating in an intensive training program [17].…”
Section: Introductionmentioning
confidence: 99%
“…In this approach, users interact with virtual objects through the movements of their hands and body, or through tactile interfaces (gloves, joysticks, mouse), performing actions in a simulated environment 7 . The invention of low-cost human movement sensors in commercial game systems has made it easier to use video games for rehabilitation 8 . Examples of these systems include the Kinect for Microsoft's Xbox ® , the Nintendo Wii ® and the PlayStationMove ® by Sony.…”
mentioning
confidence: 99%